Opportunities and challenges in the University teaching Jordan: A Jordanian PHD Women Perspective - Akroush, Lubna (Jordan Journal of Social Sciences, 2020)
This study aimed at identifying the available opportunities and challenges in the field of university teaching from the point of view of the Jordanian academies. A study was conducted on a sample of academies in Jordanian universities. The study used the method of social survey in the sample of purpose. The study community from all the Jordanian academies in all regions of the Kingdom, (1321) Jordanian Academy of PhD holders of whom (307) academic academies working in public universities, and (209( academic doctor working in private universities, the study has reached a number of results, most notably that More than half of the academies (58%) live in the Central Region, 54.8% have a PhD at their own expense, 34.6% have academic experience between 5-9 years, and 46.5% have not been assigned any administrative work at the university (32.1%). The study also reached a number of recommendations, most notably the availability of opportunities for academia to participate in academic or administrative committees outside the university, And to create specialized programs for Jordanian academies to train in managerial skills and find the field and support Time for this and taking into account the circumstances of the academies from the responsibilities of family home, and reduce the quorum of teaching them, which also allows to increase the time spent for academic research and scientific.